THE ROLE OF SOCIAL SUPPORT IN ACADEMIC RESILIENCE AMONG STUDENTS AT STATE AND PRIVATE UNIVERSITIES - Putri Wulandari; Cut Metia (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2025)
Final-year students often face intense academic demands such as thesis writing, final projects, and the pressure to graduate on time. Not all students can effectively cope with these challenges. Academic resilience becomes essential as it reflects a student’s ability to stay strong, focused, and adaptive in difficult academic situations. Resilient students generally demonstrate better emotional control, problem-solving abilities, and strong motivation to succeed. One of the external factors that significantly supports academic resilience is social support. Encouragement and care from family, peers, and lecturers can foster a sense of security, reduce academic stress, increase motivation, and maintain students’ enthusiasm for learning. This study investigates the relationship between social support and academic resilience, specifically targeting final-year students dealing with academic pressure. The research applied a quantitative correlational approach. A purposive sampling method was used to select 117 final-year students from public and private universities in Medan. Data were collected using an online questionnaire via Google Forms. Two validated instruments were used: a social support scale adapted by Fida and an academic resilience scale adapted by Setioko. Data analysis employed the Pearson product- moment correlation test using SPSS version 25. The analysis revealed a correlation coefficient of 0.493 with a p-value of 0.000, indicating a significant positive relationship between social support and academic resilience. This suggests that students who receive greater social support tend to have higher levels of resilience in facing academic challenges. The findings emphasize the importance of a strong support system in helping students manage academic stress and succeed in their final academic stages.